2007
DOI: 10.1152/ajplung.00356.2006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of interleukin-8 via an airway epithelial signaling cascade

Abstract: Airways function as an innate immune organ against airborne bacteria that are inhaled and deposited in airways. One of the mechanisms of host defense is to recruit neutrophils into airways to clear the invaders. Airway epithelial cells produce neutrophil chemoattractant interleukin (IL)-8 in response to invading bacteria. In this study we show a signaling pathway on the plasma surface of human airway epithelial NCI-H292 cells that regulate IL-8 production in response to a model inflammatory stimulus, phorbol 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
92
4
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 25 publications
10
92
4
1
Order By: Relevance
“…A similar mechanism was previously implicated in the DUOX2-dependent regulation of NF-κB activity, and the thereof resulting IL-8 production and neutrophil recruitment [45]. The closelyrelated homolog of DUOX2, DUOX1 that is also expressed in AECs was previously shown to regulate EG-FR-dependent signaling [46,47]. Additionally, DUOX1-derived H 2 O 2 was shown to regulate intracellular protein phosphatase activities [48,49].…”
Section: Rsv Interferes With the Expression Of Duox2supporting
confidence: 54%
“…A similar mechanism was previously implicated in the DUOX2-dependent regulation of NF-κB activity, and the thereof resulting IL-8 production and neutrophil recruitment [45]. The closelyrelated homolog of DUOX2, DUOX1 that is also expressed in AECs was previously shown to regulate EG-FR-dependent signaling [46,47]. Additionally, DUOX1-derived H 2 O 2 was shown to regulate intracellular protein phosphatase activities [48,49].…”
Section: Rsv Interferes With the Expression Of Duox2supporting
confidence: 54%
“…Recent studies suggest that DUOX may participate in these responses as well, as illustrated by DUOX1-mediated production of epithelial mucins, such as MUC1 and MUC5AC, in response to inflammatory mediators such as neutrophil elastase or tumor necrosis factor (TNF)-α (105,106). Similarly, DUOX1 also mediates epithelial production of the neutrophil chemokine IL-8 in response to stimulation by bacterial lipopolysaccharide (LPS) (107). Hence, DUOX1 appears to be involved in other aspects of innate host defense in addition to direct microbial killing, and participates in epithelial signaling pathways that result in increased production of various epithelial mediators.…”
Section: Functions Of Epithelial Duox: Host Defense and Intracellularmentioning
confidence: 99%
“…4) (158,159). Indeed, a number of downstream effects of P2 receptor activation, such as expression of MUC5AC, MMP-9 or IL-8 and stimulated cell migration, have been linked to activation of DUOX1 (87,105,107,108), suggesting a common association of DUOX with epithelial purinergic signaling. Intriguingly, NOX activation has similarly been associated with ATP-mediated purinergic signaling in several other mammalian cell types (160)(161)(162)(163)(164), and in NADPH oxidase-mediated wound responses in plants (165,166), which suggests that the general signaling pathway illustrated in Fig.…”
Section: Mechanisms Of Duox Activation-the Presence Of Ef-hand Camentioning
confidence: 99%
“…Maximal CXCL8 responses further require a combined activation of the three major mitogen-activated protein kinase (MAPK) cascades: extracellular signal-regulated kinase (ERK)1/2, c-Jun N-terminal kinase (JNK) and p38 [13,14]. A range of studies also suggests the involvement of the epidermal growth factor receptor (EGFR) in CXCL8 responses induced by different agents [15][16][17][18][19][20][21], and EGFR and CXCL8 expression correlate in the airway epithelium of patients with CF and severe asthma [22,23]. Accordingly, EGFR signalling has been suggested as a convergent pathway for regulation of CXCL8 and other immune responses [23].…”
mentioning
confidence: 99%
“…Accordingly, EGFR signalling has been suggested as a convergent pathway for regulation of CXCL8 and other immune responses [23]. Recent studies with endogenous and microbial ligands have shown that CXCL8 regulation by EGFR involves transforming growth factor (TGF)-a ectodomain shedding by the metalloprotease tumour necrosis factor-a-converting enzyme (TACE)/ADAM-17 [20,21,24,25]. Whether organic or inorganic PM components regulate CXCL8 through similar mechanisms remains to be elucidated.…”
mentioning
confidence: 99%